Assessing Applicant Employability Using Social Media for Talent Acquisition and Recruitment in IT/BPM Companies (Recoletos Multidisciplinary Research Journal, 2019)
The study aims to assess the extent of social media usage in talent acquisition in IT/BPM companies in Cebu and evaluate the insights of the applicants on the practice of using social media in character assessment for hiring decision. The quantitative method was employed to obtain data from two groups of respondents which constitute thirty hiring managers and ninety-six applicants. The study found that while hiring managers moderately practice social media background check to obtain additional information about the applicant, they seldom used it in hiring decisions because of the lack of formal or informal policy allowing or restricting the use of social media for that purpose. It is also found that there is a significant difference in perception between hiring managers and prospective applicants on usergenerated content on candidate social media profile.
Keywords: social media; background check; cyber-vetting; character assessment